2018
DOI: 10.3389/fendo.2018.00088
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Ongoing Modeling-Based Bone Formation in Human Femoral Head Trabeculae via Forming Minimodeling Structures: A Study in Patients with Fractures and Arthritis

Abstract: Bone modeling is a biological process of bone formation that adapts bone size and shape to mechanical loads, especially during childhood and adolescence. Bone modeling in cortical bone can be easily detected using sequential radiographic images, while its assessment in trabecular bone is challenging. Here, we performed histomorphometric analysis in 21 bone specimens from biopsies collected during hip arthroplasty, and we proposed the criteria for histologically identifying an active modeling-based bone formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…From biopsies in subjects undergoing total hip arthroplasty or femoral head replacement, Sano et al revealed strong histomorphometric evidence of MBBF on trabeculae in loaded femoral heads, even in elderly subjects. (34) Thus, bone in the femoral neck may hold greater potential for modeling because it is weight bearing. Additional studies are needed to address bone histomorphometry and levels of MBBF and RBBF in the femoral neck in the untreated population and those who have been treated with denosumab.…”
Section: Discussionmentioning
confidence: 99%
“…From biopsies in subjects undergoing total hip arthroplasty or femoral head replacement, Sano et al revealed strong histomorphometric evidence of MBBF on trabeculae in loaded femoral heads, even in elderly subjects. (34) Thus, bone in the femoral neck may hold greater potential for modeling because it is weight bearing. Additional studies are needed to address bone histomorphometry and levels of MBBF and RBBF in the femoral neck in the untreated population and those who have been treated with denosumab.…”
Section: Discussionmentioning
confidence: 99%
“…2). Note that with respect to a previous study, ( 25 ) we have abandoned the requirement of a relatively lower mineralization based on the fluorescent signal since we now consider the osteoid seam to be sufficient evidence for a state of active modeling. The N.FMiS/T.Ar was averaged over the three separated sections.…”
Section: Methodsmentioning
confidence: 97%
“…Our histological identification of a FMiS on a trabecular surface does not rely on fluorochrome prelabeling. ( 25 ) Instead, it is defined by the following criteria: the base of the FMiS is a smooth and lamellar BS, the lamellar pattern of the FMiS is different from the underlying bone tissue, and the surface of the FMiS is covered with an osteoid seam (Fig. 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, Kobayashi et al (2003) emphasized that minimodeling should be taken into an account when dealing with parameters related to osteoid volume and mineralization, and therefore, supported Frost's hypothesis that minimodeling can continue throughout human life. Sano et al (2018) followed Kobayashi's study to examine bone histomorphometry in 21 bone specimens collected during hip arthroplasty. They proposed that active modeling-based bone formation can be referred to as "forming minimodeling structure".…”
Section: Introductionmentioning
confidence: 99%